Arthropod species of the Mariepskop Summit, Mpumalanga Province, South Africa : Affinities with Afromontane Natal Drakensberg fynbos and Cape fynbos - Ferguson, Willem (University of Pretoria, 2021)
Dissertation (MSc (Environmental Ecology))--University of Pretoria, 2020.